ABOUT THE FINANCIAL REPORTING ON THE CAPITAL MARKETS IN THE EUROPEAN UNION: REQUIREMENTS OF USING THE IFRS AND THE EQUIVALENCE OF THIRD COUNTRY ACCOUNTING STANDARDS - Rotila, Aristita (Studies and Scientific Researches. Economics Edition, 2013)
The need to build a single European market and to ensure the competitiveness of the community capital markets led to the involvement of European Union in the convergence process taking place on a global level in the realm of financial reporting. This paper is a study on financial reporting for the capital markets in the European Union by analyzing the accounting standards that need to be applied. Specifically, this paper highlights a number of issues concerning: the adoption of IAS / IFRS in the European Union and their compulsory aspect in preparing the consolidated financial statements for the companies listed on a regulated market; the requirement’s extension of using the IFRSs adopted in the European Union to the issuers of certain third countries involving a public offer of securities in European Union or performing transactions with securities on a community regulated market; the establish of a mechanism for the determination of equivalence of certain third country accounting standards with IFRSs in force at European level and, consequently, the possibility of using by some third country issuers, in preparing the consolidated financial statements submitted to the European markets, recognized national standards as equivalent to adopted IFRS.